Responsibilities of Regency/Municipal Governments in Managing Basic Education Affairs - Yohanes Pattinasarany (SASI, 2022)
Introduction: The handover of basic education affairs by the central government to regencies/municipalities, raises the responsibility of district/city local governments to manage basic education affairs in order to provide quality basic education to local community members.